A survey of inclusive growth policy - Almas Heshmati; Jungsuk Kim; Jacob Wood (Economies, 2019)
Background: Since the latter part of the 20th Century, countries have been particularly challenged by the trade-off that exists between delivering generous welfare provisions and strong economic growth. Such dynamics have stimulated a need to better understand the causes of income inequality so as to better formulate policies that foster inclusive growth and reduce growing concerns surrounding income inequality. Method: Given its ability to succinctly summarize, analyze, and synthesize an extant body of literature from a certain genre of scholastic endeavor, this study utilizes a literature review as its proposed methodological approach. Results: From our assessment of the literature, we identified four key areas that contribute significantly to income inequality in both advanced and developing economies, these include: (i) pursuing skill-biased technological change; (ii) enhancing education systems; (iii) consolidation of globalization; and (iv) reform of the labor market and its relevant institutions. Conclusion: There is no silver bullet to achieving inclusive growth. Any policy manifesto must seek to offer a coordinated policy platform that looks to deal directly with the causes of inequality. In order to do so, consideration should be given to a range of policy areas including fiscal, education, trade liberalization, and labor market reforms.
Keywords: D63; E62; I32; I38; J68; O47; P46; 330; income inequality; poverty reduction; equity; inclusive growth; fiscal policy; developing Asia; advanced welfare economies